SISTEM INFORMASI PENDATAAN ANGGOTA INTERNET CLUB UNIVERSITAS STIKUBANK SEMARANG MENGGUNAKAN FRAMEWORK CODE IGNITER (Information Technology and Telematics, 2013)
Data collection systemand amemberofthe InternetClubevent is stillusing conventionalmethods(manual) whichallows theloss ofthedatarelated tothe activitiesanddataarchivingInternetClubmembers.  Associated with the developmentofadvanced technology, the data collection systemcan be optimized and maximizedby creating a system that aims to replace conventional systems.The purpose of this information system is to speedup the work, time, efficiency, and preservationarchiving at UKM Internet Club UnisbankSemarang.  Logging information system wasdesigned with UML (Unified Modelling Language) and made using codeigniter framework asprogramming language and MySql as the database.The system is expected to be able to support thearchivingdata regularly sowillprovidebenefitsandmakes it easy formembersto findtheevent andandcouldbecome the benchmarkforeventsto come.Keywords: information systems, Logging,Codeigniter, MySQL